A previously undescribed hernia containing an acutely inflamed appendix—case report and review of management on hernias containing the vermiform appendix - Bain, Kevin; Morin, Nicholas; Meytes, Vadim; Glinik, Galina (Laparoscopic Surgery, 2018)
Hernias involving the appendix are unusual and are often found during surgical exploration. The rarity of these hernias makes it difficult to discuss standard of treatment. When an acutely inflamed appendix is encountered within a hernia, appendectomy should be performed with primary repair of the hernia. This case documents the unique finding of an appendix herniating through a previously undescribed region in the abdominal wall found in a patient presenting with acute appendicitis.